SENIOR HIGH SCHOOL TEACHING: A PHENOMENOLOGICAL INQUIRY - Remedios Cabaral Bacus; Rivika Coronado Alda (UUM Press, 2022)
Purpose - This study aims to explore the teachers' lived experiences in Senior High School teaching.The K to 12 program is one curricular reform in the Philippines to ascertain that basic education graduates possess the required competencies at par with the international standards. Methodology - In this qualitative study, 15 Senior High School (SHS) teachers' lived experiences were explored to arrive at the essence of SHS teaching at the onset of curriculum implementation. Using Husserlian phenomenological design and Colaizzi's method of data analysis, three themes emerged from the in-depth interviews: expectations and apprehensions, experiences and strategies, and attitude and aspirations. The teachers have acknowledged their important roles and have remained optimistic despite the program's limitations. Their unique experiences as they grapple with their new teaching assignment enthused them to explore ways to assist them in the teaching process. Findings - The findings provide academic institutions with input to revisit policies of SHS implementation by charting relevant trainings geared toward teachers' professional development,  conducting regular onsite monitoring, and providing need-based support and resources for teachers' up-skilling and re-skilling. Significance - With the requirements towards SHS implementation and the teachers' collective aspirations, the Department of Education can continue to provide inclusive and equitable education for all.